Nasal and Vaginal Vaccinations Have Differential Effects on Antibody Responses in Vaginal and Cervical Secretions in Humans - Johansson, Eva-Liz (American Society for Microbiology, 2001)
Sexually transmitted diseases are a major health problem worldwide, but there is still a lack of knowledge about how to induce an optimal immune response in the genital tract of humans. In this study we vaccinated 21 volunteers nasally or vaginally with the model mucosal antigen cholera toxin B subunit and determined the level of specific immunoglobulin A (IgA) and IgG antibodies in vaginal and cervical secretions as well as in serum. To assess the hormonal influence on the induction of antibody responses after vaginal vaccination, we administered the vaccine either independently of the stage in the menstrual cycle or on days 10 and 24 in the cycle in different groups of subjects. Vaginal and nasal vaccinations both resulted in significant IgA and IgG anti-cholera toxin B subunit responses in serum in the majority of the volunteers in the various vaccination groups. Only vaginal vaccination given on days 10 and 24 in the cycle induced strong specific antibody responses in the cervix with 58-fold IgA and 16-fold IgG increases. In contrast, modest responses were seen after nasal vaccination and in the other vaginally vaccinated group. Nasal vaccination was superior in inducing a specific IgA response in vaginal secretions, giving a 35-fold increase, while vaginal vaccination induced only a 5-fold IgA increase. We conclude that a combination of nasal and vaginal vaccination might be the best vaccination strategy for inducing protective antibody responses in both cervical and vaginal secretions, provided that the vaginal vaccination is given on optimal time points in the cycle.